Structural And Semantic Aspects of Lexemic Units Expressing National Value in English and Uzbek Languages - Shamsematova Barno Rikhsivayevna (Genius Journals, 2021)
This article discusses that the study of values is one of the current areas in linguistics that requires in-depth analysis and research. In addition, the structure of concepts representing national values in English and Uzbek has been studied in several groups.
Keywords: National Values; Lexeme Units; Structural-Semantic Analysis